Математична модель оптимального вибору засобів захисту інформації в інформаційній системі - Пшеничних, С. В.; Добринін, І. С.; Клочкова, Д. Ю. (ХНУРЕ, 2023)
The report examines and addresses the problem of optimal selection of information security measures against security threats in the design of a comprehensive information protection system within an information system. To choose security measures, a new efficiency indicator is proposed, allowing consideration of the implementation and operational costs of a particular measure, along with its capability to simultaneously protect against multiple threats. Based on this indicator, a criterion for the optimal selection of security measures against security threats is suggested for each information resource of the information system
Keywords: засоби захисту інформації; захист інформації